Pengaruh Unsur-Unsur Komunikasi Pelatihan Terhadap Kinerja Karyawan Pusat Pengembangan Sumber Daya Manusia Badan Narkotika Nasional Lido - Asyam Hilmi Fawwaz; Tiara Puspanidra; Annory Langga’O (Universitas Pakuan, 2026)
The issue regarding training institutions is very important for an organization (government), and an appropriate communication strategy is needed to convey messages effectively. Communication is very important for building cooperation among members of the organization and influencing the process of achieving organizational goals. For training designers, improving the performance of the training that is followed aims to analyze how training can improve employee performance. Successful organizational communication helps the entire organization to establish relationships. To improve organizational performance, there must be a conducive communication environment that allows for good interaction between subordinates and fellow subordinates, as well as between superiors and subordinates. The purpose of this study is to describe the elements of training communication, the performance of employees involved, and to analyze the influence of training communication elements on employee performance. The research method used is a quantitative approach with a descriptive design. Using regression analysis, determination, and data collected from 36 employees who had undergone training through surveys and interviews, the results showed a significant positive influence between training and employee performance, with training contributing 48.1% to performance improvement. In conclusion, effective training communication is crucial for improving employee performance, although other factors must also be considered to achieve optimal results. This study is expected to contribute to the development of training programs within the National Narcotics Agency's Human Resource Development Center.